Mismatch Extension During Strong Stop Strand Transfer and Minimal Homology Requirements for Replicative Template Switching During Moloney Murine Leukemia Virus Replication - Marr, Sharon Fodor (J Mol Biol, 2003)
Reverse transcription requires two replicative template switches, called minus and plus strand strong stop transfer, and can include additional, recombinogenic switches. Donor and acceptor template homology facilitates both replicative and recombinogenic transfers, but homology-independent determinants may also contribute. Here, improved murine leukemia virus-based assays were established and the effects of varying extents of mismatches and complementarity between primer and acceptor template regions were assessed. Template switch accuracy was addressed by examining provirus structures, and efficiency was measured using a competitive titer assay. The results demonstrated that limited mismatch extension occurred readily during both minus and plus strand transfer. A strong bias for correct targeting to the U3/R junction and against use of alternate regions of homology was observed during minus strand transfer. Transfer to the U3/R junction was as accurate with five bases of complementarity as it was with an intact R, and as few as 3 nt targeted transfer to a limited extent. In contrast, 12 base recombinogenic acceptors were utilized poorly and no accurate switch was observed when recombination acceptors retained only five bases of complementarity. These findings confirm that murine leukemia virus replicative and recombinogenic template switches differ in homology requirements, and support the notion that factors other than primer–template complementarity may contribute to strong stop acceptor template recognition.